Precise Regulation Strategy for Fluorescence Wavelength of Aggregation‐Induced Emission Carbon Dots - Liu Ding; Xilang Jin; Yuchong Gao; Shouwang Kang; Haiyan Bai; Xuehao Ma; Taotao Ai; Hongwei Zhou; Weixing Chen (Advanced Science)
Abstract Aggregation‐induced emission (AIE) carbon dot (CDs) in solid state with tunable multicolor emissions have sparked significant interest in multidimensional anti‐counterfeiting. However, the realization of solid‐state fluorescence (SSF) by AIE effect and the regulation of fluorescence wavelength in solid state is a great challenge. In order to solve this dilemma, the AIE method to prepare multi‐color solid‐state CDs with fluorescence wavelengths ranging from bright blue to red emission is employed. Specifically, by using thiosalicylic acid and carbonyl hydrazine as precursors, the fluorescence wavelength can be accurately adjusted by varying the reaction temperature from 150 to 230 °C or changing the molar ratio of the precursors from 1:1 to 1:2. Structural analysis and theoretical calculations consistently indicate that increasing the sp2 domains or doping with graphite nitrogen both cause a redshift in the fluorescence wavelength of CDs in the solid state. Moreover, with the multi‐dimensional and adjustable fluorescence wavelength, the application of AIE CDs in the fields of multi‐anti‐counterfeiting encryption, ink printing, and screen printing is demonstrated. All in all, this work opens up a new way for preparing solid‐state multi‐color CDs using AIE effect, and further proposes an innovative strategy for controlling fluorescence wavelengths.